Corporate Governance: An Ethical Perspective - Arjoon, Surendra (Journal of business ethics, 2005)
This paper discusses corporate governance issues from a compliance viewpoint. It makes a distinction between legal and ethical compliance mechanisms and shows that the former has clearly proven to be inadequate as it lacks the moral firepower to restore confidence and the ability to build trust. The concepts of freedom of indifference and freedom for excellence provide a theoretical basis for explaining why legal compliance mechanisms are insufficient in dealing with fraudulent practices and may not be addressing the real and fundamental issues that inspire ethical behavior. The tendency to overemphasize legal compliance mechanisms may result in an attempt to substitute accountability for responsibility and may also result in an attempt to legislate morality which consequently leads to legal absolutism. The current environment of failures of corporate responsibility are not only failures of legal compliance, but more fundamentally failures to do the right (ethical) thing.